(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2015)
Events currently constitute one of the main categories of the tourist product. They are included in the group of the so-called simple tourist products. Their significance on the market of tourist services is constantly increasing. Events constitute a modern form of the promotion of a brand and a product; they facilitate access to new customers, and also create a positive image of a tourist destination. It should be emphasized that for many tourists, events constitute one of the main purposes of a tourist trip. This means that they are an essential element of the tourist attraction of a given place. In this article, the potential was demonstrated of events organized in Kołobrzeg in the context of their functioning as the products of cultural tourism. A research thesis was accepted that organization of events currently constitutes one of the main factors that determine the development of cultural tourism in a given area.